2011
DOI: 10.1002/jqs.1503
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene environmental conditions in Coronation Gulf, southwestern Canadian Arctic Archipelago: evidence from dinoflagellate cysts, other non‐pollen palynomorphs, and pollen

Abstract: Boxcore 114.1868 W; 211 m water depth) from Coronation Gulf represents the first decadalscale marine palynology and late Holocene sediment record for the southwestern part of the Northwest Passage. The record was studied for organic-walled microfossils (dinoflagellate cysts, non-pollen palynomorphs), pollen, terrestrial spores, and sediment characteristics. 210 Pb, 137 Cs, and three accelerator mass spectrometry 14 C dates constrain the chronology. Three prominent palaeoenvironmental zones were identified. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 99 publications
(229 reference statements)
7
54
0
Order By: Relevance
“…The foraminiferal linings are the microforaminifera organic part and is always related to the marine conditions (Stancliffe, 1996). This concentration difference between the two cores may be related to different environmental conditions, related for instance to higher salinity at this local or to the high productivity as observed by Pienkowski et al (2011) in southwestern Canadian Artic Archipelago.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The foraminiferal linings are the microforaminifera organic part and is always related to the marine conditions (Stancliffe, 1996). This concentration difference between the two cores may be related to different environmental conditions, related for instance to higher salinity at this local or to the high productivity as observed by Pienkowski et al (2011) in southwestern Canadian Artic Archipelago.…”
Section: Discussionmentioning
confidence: 85%
“…This algae genus can occur in freshwater as environments with a certain salinity (Traverse, 2008). Pienkowski et al (2011) found this colonial alga in the Coronation Gulf and associated its occurrence with increasing fluvial input.…”
Section: Discussionmentioning
confidence: 95%
“…The earliest known occurrences are from the Lower Triassic of Ireland and Israel (Van Waveren, 1994) and the Lower Cretaceous of France (Gorin & Steffen, 1991). Although there are several gaps in the fossil record of this group, tintinnid organic remains are frequent only from Holocene marine deposits (Reid, 1975;Reid & John, 1978;Grill et al, 2002;Roncaglia, 2004;Borromei & Quattrocchio, 2001Meckler et al, 2008;Mudie et al, 2010;Pienkowski et al, 2011Pienkowski et al, , 2013, and may aid in understanding recent environmental changes (Grill et al, 2002;Roncaglia, 2004;Borromei & Quattrocchio, 2001Meckler et al, 2008;Mudie et al, 2010).…”
Section: Stratigraphymentioning
confidence: 99%
“…Nevertheless, many loricae and cysts are recovered by palynological processing (Reid & John, 1978;Meckler et al, 2008;Mudie et al, 2010Mudie et al, , 2011Pienkowski et al, 2011Pienkowski et al, , 2013, being classified within the palynomorphs as zoomorphs (Traverse, 1994). In modern marine sediments, a large quantity and variety of tintinnid cysts and loricae is known (Reid, 1975;Reid & John, 1978;Van Waveren, 1994;Van Waveren & Visscher, 1994;Kawamura, 2004;Hardy & Wrenn, 2009;Lipps et al, 2013;Pienkowski et al, 2011Pienkowski et al, , 2013Matsuoka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation